Exposure of Children to Rural Lifestyle Factors Associated With Protection Against Allergies Induces an Anti-Neu5Gc Antibody Response - Frei, Remo; Roduit, Caroline; Ferstl, Ruth; O'Mahony, Liam; Lauener, Roger P. (Frontiers in Immunology, 2019)
Rural lifestyle has been shown to be highly protective against the development of allergies. Contact to farm-animals or pets and early-life consumption of milk products that turned out to be important. These exposures provide contact to N-glycolylneuraminic acid (Neu5Gc), a sialic acid naturally expressed in mammalians but not in humans or microbes although both are able to incorporate exogenously provided Neu5Gc and induce thereby and anti-Neu5Gc antibody response. Farmers’ children had elevated levels of anti-Neu5Gc antibodies associated with increased contact to Neu5Gc. Farm-related exposures that were associated with protection against allergies such as exposure to farm-animals or pets and consumption of milk were also associated with an antibody response to Neu5Gc in children. Exposure to cats was associated with increased anit-Neu5Gc IgG levels at different timepoints assessed between one year of age and school-age. Moreover, consumption of non-pasteurized milk in the first year of life was associated with increased anti-Neu5Gc IgG levels. Neu5Gc-providing exposures that were associated with protection against allergies were reflected in an elevated anti-Neu5Gc IgG level in children. Exposure to Neu5Gc was associated with anti-inflammation and protection of asthma development in children and mice without contribution of anti-Neu5Gc antibodies.